Optimizing the Extraction and Encapsulation of Mucilage from Brasenia Schreberi - Luo, Qingying (Polymers (Basel), 2019)
The mucilage from Brasenia schreberi (BS) exhibits various biological activities, including antialgal, antibacterial, soluble-fiber properties, and excellent lubricating behavior. Thus, the extraction and wide use of mucilage in the food industry are crucial. In this study, the high-speed shear-assisted extraction of mucilage from BS was optimized by using response surface methodology (RSM). The optimal extraction conditions were as follows: Extraction temperature of 82 °C, extraction time of 113 min, liquid–solid ratio of 47 mL/g, and shear speed of 10,000 rpm. Under these conditions, the actual yield of BS mucilage was 71.67%, which highly matched the yield (73.44%) predicted by the regression model. Then, the BS mucilage extract was powdered to prepare the capsule, and the excipients of the capsule were screened using a single-factor test to improve the disintegration property and flowability. The final capsule formulation, which consisted of: 39% BS mucilage powder (60 meshes); 50% microcrystalline cellulose (60 meshes) as the filler; both 10% sodium starch glycolate and PVPP XL-10 (3:1, 60 meshes) as the disintegrant; both 1% colloidal silicon dioxide and sodium stearyl fumarate (1:1, 100 meshes) as the glidant by weight; were used for preparing the weights of a 320 mg/grain of capsule with 154.7 ± 0.95 mg/g polysaccharide content. Overall, the optimized extraction process had a high extraction rate for BS mucilage and the capsule formulation was designed reasonably.